Distribution and risk assessment of trace metals in multifarious matrices of Vembanad Lake system, Peninsular India. (August 2019) - ShyleshChandran, M.S.; Ramasamy, E.V.; Mohan, Mahesh; N, Sruthi S.; Jayasooryan, K.K.; Augustine, Toms; Mohan, Kannan
Abstract: Trace metal contamination in aquatic ecosystems is of significant concern in countries like India having a recent industrial history. The present study mainly focuses on the spatial and temporal distribution, occurrence and toxicity of five trace metals (Hg, Cd, Zn, Cu and Pb) in water and sediment matrix of Vembanad Lake system (VLS), India. Mercury analysis was done by using Cold Vapor Atomic Fluorescence Spectrometer, and the other metals were analysed using Volta metric-Trace metal analyser. The spatial distribution of trace metals in the study area showed the following trends, Zn > Pb > Cu > Cd > Hg, Zn > Pb > Cu > Hg > Cd for surface water and bottom water respectively. Health risk assessment on human population associated with trace metals was also calculated to predict their health impacts on human through non-dietary exposure. The trace metals contamination in water and sediments of VLS are potential to cause cancer on human population associated with the system. Ecological risk indices showed that the northern portion of VLS is more contaminated with trace metal than the other part of the system. Highlights: Study focuses on distribution and toxicity of 5 trace metals in water and sediment. Human health risk by metals was determined to predict possible health impact. Metal contamination in water and sediments has potential to cause cancer on humans. Indices have been used to identify possible sources of metal input to the system. Indices show that northern portion of lake was more contaminated with metals.